Access to marine ecosystem services: Examining entanglement and legitimacy in customary institutions. (February 2020) - Lau, Jacqueline D.; Cinner, Joshua E.; Fabinyi, Michael; Gurney, Georgina G.; Hicks, Christina C.
Highlights: Examines access to marine provisioning ecosystem services in Papua New Guinea. Draws on theory of entanglement to extend theoretical treatment of uneven access. Legitimacy of customary institutions to shape access is socially differentiated. Ecosystem services would benefit from a relational definition of power. Abstract: Ecosystem services have become a dominant paradigm for understanding how people derive well-being from ecosystems. However, the framework has been critiqued for over-emphasizing the availability of services as a proxy for benefits, and thus missing the socially-stratified ways that people access ecosystem services. We aim to contribute to ecosystem services' theoretical treatment of access by drawing on ideas from political ecology (legitimacy) and anthropology (entanglement). We hypothesize that where customary and modern forms of resource management co-exist, changes in customary institutions will also change people's ability to and means of benefiting from ecosystem services, with implications for well-being. We ask a) what are the constellations of social, economic, and institutional mechanisms that enable or hinder access to a range of provisioning ecosystem services; and b) how are these constellations shifting as different elements of customary institutions gain or lose legitimacy in the process of entanglement with modernity? Through a qualitative mixed-methods case study in a coastal atoll community in Papua New Guinea, we identify key access mechanisms across the value chain of marine provisioning services. Our study finds the legitimacy of customary systems – and thus their power in shaping access – has eroded unevenly for some ecosystem services, and some people within the community (e.g. younger men), and less for others (e.g. women), and that different marine provisioning services are shaped by specific access mechanisms, which vary along the value chain. Our findings suggest that attention to entanglement and legitimacy can help ecosystem services approaches capture the dynamic and relational aspects of power that shape how people navigate access to resources in a changing world. We contend that viewing power as relational illuminates how customary institutions lose or gain legitimacy as they become entangled with modernity.